Data Analytics Tool For Logistic Planning and Event Management - Sukiman, Muhammad Hasif Syafiq (IRC, 2019)
This research is focused on the tourism operation using data analytics. Data is getting bigger where we can get from many kind of sources. Visualization, historical data, websites, and unstructured sources such as crowd sourcing to collect data like through surveys. Some of data that have been collected will be generated as a forecast analysis which some of it to be used for tourism. The implementation of data analytics in tourism industry specifically on domestic which focusing on tourist or local citizens travelling in Malaysia to improve how can people travel with the peace of mind. This research is to help people when going travel to anywhere without facing problems such as traffic jam, hotels are fully booked, and transportation cannot be found due to a lot of demands. One of the research purpose of this project is to see how travelling management tool can help people to travel and using historical data where we can see the places is predicted to be a lot of tourist. The scope of the project will be focused on tourist and citizen’s behavior in Malaysia. The core objective is to look into helping user to manage their logistics during their travelling period and determining the needs of travelers. Travel management tool using data analytics is a system that will check whether it is okay to travel at a certain period with the assistance of analytic tool. It is very crucial for customers to have the best time to arrive their destination within time. It is advised for the accommodation management to check if there is no obstacle to set a target when customer need to book for hotel room. The requirements will be gathered from surveys, observation and few findings which will be from results of how people want the data to be presented which will help to complete the system and development of the prototype.